Concussion incidence by type of sport: Differences by sex, age groups, type of session, and level of play - an overview of systematic reviews with meta-analysis - Matias-Soto, J.; Infante-Cano, M.; García-Muñoz, C.; Pineda-Escobar, S.; Martinez-Calderon, J. (Journal of Orthopaedic & Sports Physical Therapy, 2024)
OBJECTIVES: To (1) summarize pooled prevalence and incidence rates of concussion by type of sport and (2) synthesize the differences in prevalence or incidence rates of concussion by type of sports in terms of sex, age, type of session, and level of competition.